2018
DOI: 10.1007/s10661-018-6858-1
|View full text |Cite
|
Sign up to set email alerts
|

Urban green area provides refuge for native small mammal biodiversity in a rapidly expanding city in Ghana

Abstract: Urbanization is a key driver of global biodiversity loss. Although sub-Saharan African countries are experiencing unprecedented urbanization and urban expansion, very little is known about how this impacts tropical biodiversity. Here, we assessed the effects of urban expansion and urban green space on local small mammal species diversity in Accra, Ghana. We surveyed small mammals in the University of Ghana botanical garden, an urban green area (UGA) and adjoining built-up environment (BE) and compared the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…From an ecosystem services approach, the study's outcomes support the view that trees can be an important ecosystem service provider in urban areas. In addition to ecosystem services such as capturing air and water pollutants, providing shade and habitat, and decreasing CO2 emissions (Hirokawa et al, 2011;Niemelä et al, 2010;Nowak et al, 2006;Ofori et al, 2018;Soares et al, 2011), urban trees may provide another ecosystem service: improving perceptions of neighborhood safety.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an ecosystem services approach, the study's outcomes support the view that trees can be an important ecosystem service provider in urban areas. In addition to ecosystem services such as capturing air and water pollutants, providing shade and habitat, and decreasing CO2 emissions (Hirokawa et al, 2011;Niemelä et al, 2010;Nowak et al, 2006;Ofori et al, 2018;Soares et al, 2011), urban trees may provide another ecosystem service: improving perceptions of neighborhood safety.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Specifically, urban trees contribute to countering the effects of climate change by decreasing atmospheric carbon dioxide (CO2) through the processes of carbon storage and sequestration (Liu & Li, 2012;Nowak et al, 2013). Trees also increase biodiversity by providing shelter for various species (Ofori et al, 2018), improve air quality in cities (Nowak et al, 2006), improve resilience to flooding by providing storm water attenuation (Roy et al, 2012), and help reduce energy demands (Roy et al, 2012;Soares et al, 2011). These environmental benefits as well as the aesthetic, amenity, and shading benefits of urban trees generate economic benefits that usually outweigh relevant costs (Soares et al, 2011;Song et al, 2018).…”
Section: Urban Tree Covermentioning
confidence: 99%
“…With such rapid urban changes, serious coordination deficits (50) in urban planning and development strategies might occur. For instance, planned and unplanned buildings will likely reduce green areas in cities, resulting in biodiversity loss (46,100) and an increase in urban heat island effects (87,126). Both phenomena have negative impacts on human health and well-being (118), and studies from other parts of the world show that urban green areas are associated with mental health (77,117).…”
Section: Rapid Urbanizationmentioning
confidence: 99%
“…Additionally, this growth often happens faster than infrastructure can accommodate. The potential "coordination deficit" (Hill et al, 2014) poses a risk to urban green areas and existing biodiversity there within (Güneralp et al, 2017;Ofori et al, 2018), as buildings and other supporting structures are constructed-at times without adequate planning. Studies from other parts of the world (Lee and Maheswaran, 2011;Saulle and La Torre, 2011) and South Africa (Tomita et al, 2017) have found that green spaces, particularly in urban environments, have ameliorating effects on mental health and well-being and facilitate physical activity and social contact (World Health Organization, 2016c).…”
Section: Introductionmentioning
confidence: 99%